2018
DOI: 10.1007/s00204-018-2186-z
|View full text |Cite
|
Sign up to set email alerts
|

Human-relevant potency threshold (HRPT) for ERα agonism

Abstract: The European Commission has recently proposed draft criteria for the identification of endocrine disrupting chemicals (EDCs) that pose a significant hazard to humans or the environment. Identifying and characterizing toxic hazards based on the manner by which adverse effects are produced rather than on the nature of those adverse effects departs from traditional practice and requires a proper interpretation of the evidence regarding the chemical’s ability to produce physiological effect(s) via a specific mode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 109 publications
(133 reference statements)
3
32
0
Order By: Relevance
“…Lately Borgert et al [ 19 ] proposed a Human Relevant Potency Threshold (HRPT) for chemicals acting on the estrogen receptor. This approach is based on a comparison of in vitro potency with in vivo effects in either uterotrophic assays or from human clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…Lately Borgert et al [ 19 ] proposed a Human Relevant Potency Threshold (HRPT) for chemicals acting on the estrogen receptor. This approach is based on a comparison of in vitro potency with in vivo effects in either uterotrophic assays or from human clinical evidence.…”
Section: Discussionmentioning
confidence: 99%
“…The view that in vitro oestrogen receptor activation potencies of the linear n -alkyl parabens are not sufficiently high to act via an oestrogenic mode-of-action in humans (Watanabe et al 2013 ; Borgert et al 2018 ) is further supported by aggregate exposure assessments in humans: for methyl paraben, ethyl paraben and propyl paraben, aggregate exposure assessments addressing oral, dermal and inhalation exposures to personal care products, medicinal products and food (as three major sources of exposure) revealed estimates of approx. 7.2 and 4.5 mg/kg bw/day for human external and internal exposures, respectively (Brand et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…These observations further support the decision to focus only on the shorterchained linear n-alkyl parabens in the category approach to interpolate missing data for ethyl paraben. Borgert et al (2018) have suggested a human-relevant potency threshold for oestrogen receptor α agonism of 10 -4 relative to the potency of 17β-estradiol as minimum level of mechanistic potency necessary for a chemical to be able to act via this mode-of-action in humans. Following this threshold, none of the in vitro oestrogen receptor activation potencies of the linear n-alkyl parabens (Watanabe et al 2013) are sufficiently high to act via an oestrogenic modeof-action in humans.…”
Section: Follow-up Of Concern For Endocrine Disrupting Potential Of Pmentioning
confidence: 99%
“…Otherwise, they cannot displace the numerous natural endogenous ligands present. This explains, for example, why S-EDCs with low relative potency have never been shown to exhibit estrogenic effects in humans (Borgert et al 2018 ). Potency and concentrations define the minimum requirement for influencing endocrine activity.…”
Section: Biochemical Principles Of Interaction At Receptors or Enzymementioning
confidence: 99%